Utilization of urine protein/creatinine ratio in pregnancy for diagnosis of preeclampsia - Bhadarka, Nagajan; Poddar, Krutika; Joshi, Satyam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the present study was to evaluate the ability of the random urine P/C ratio to predict significant proteinuria, as well as to introduce a diagnostic test for preeclampsia that would avoid the inconvenience and time consumption of 24-hour urine protein collection. Methods: A total of 100 women who were pregnant were included in the study. For urine test, the urine was collected for 24 hours. The women patients provided the mid stream urine sample prior to the collection period. Biuret colorimetric assay was used to determine the total protein in the urine and the creatinine concentration was measured with the help of modified Jaff test. Results: The mean urinary protein excretion in 24 hour urine collection was found to be 2.05±0.74 g/dl and the median serum creatinine concentration was found to be 0.82 mg/dl. The mean p/c ratio was found to be 1.94±0.83. The correlation coefficient for the p/c ratio against the 24 hour urine protein excretion was found to be 0.88. Conclusions: This test can also be used as a reasonable alternative to 24-hour urine protein excretion, especially in emergency situations, and, it could also complement the urinary dipstick test in preeclamptic pregnancy.